Pemanfaatan Teknologi Gadget Sebagai Sosialisasi dan Edukasi Ibu PKK Kelurahan Kedurus Surabaya - Lucky Kurniawan Mahardiko; Sella DS; Nisfa AS; Wishal FK; Laylyyatus SN; M. Arkansyah Arkansyah (Prapanca : Jurnal Abdimas, 2021)
The Family Welfare Development Organization (PKK) Rukun Warga (RW) 02 located at Balai RW 02, Kedurus Village, Karang Pilang District, Surabaya City, East Java is a community organization that empowers women. Located in Balai Rukun Warga (RW) 02, Kedurus Village, Karang Pilang District, Surabaya City has 27 members, each of which is represented from 9 Rukun Tangga (RT) where each RT has 3 members. The activities of the RW 02 Family Welfare Guidance women are holding regular monthly meetings, controlling and implementing reforestation movements, cultivating clean and healthy living, planting TOGA plants, educational counseling, fostering RW competitions, bazaar activities to support the economic and social sector. other. After looking for some data and interviews with the PKK RW 02 administrators, Kedurus Village, Karang Pilang District, the administrators have limited optimal use of gadgets through video to support their activities as business women and a mother in terms of supporting children using gadgets for learning and making business promotion videos. they.